Improved secant method for getting proper initial magnetization in transformer DC bias simulation. (December 2018) - Lu, Hailiang; Zhang, Jingzhuo; Yang, Fenyan; Xu, Baiyu; Liu, Zhengfu; Zheng, Zhihui; Lan, Lei; Wen, Xishan
Highlights: A simulation model of transformer under DC bias is proposed. The influence of initial magnetization on simulation process is analyzed. An improved secant method for getting proper initial magnetization is proposed. Abstract: Geomagnetically – Induced Currents (GIC) and monopole operation of high voltage direct current (HVDC) both can cause transformer DC bias, and Jiles-Atherton (JA) model is effective in transformer DC bias simulation while the influence of initial magnetization is neglected in existing papers. In this paper, the influence of initial magnetization and magnetizing current on simulation process are analysed based on the presented simulation model, and the conclusion that initial magnetization has evident influence while initial magnetizing current has not is reached. The trend of magnetizing current is valued by representative slope of envelop curve, then an improved secant method for getting proper initial magnetization is proposed basing on the slope. With the method, the dependence of proper initial magnetization on DC current and closing angle are presented, and the mechanization is analysed.